'Add to cart': prison-based community service for psychologists in South Africa and the comfort of online shopping. Issue 3 (3rd July 2021) - Salie, Mariam; Snow, Megan; De Wet, Henri; Marquard, Kryska; Swartz, Leslie
Abstract : To register as independent practitioners in South Africa, all clinical psychologists must first complete a compulsory year of community service. We report here on an aspect of our reactions to completing this service in prison contexts, where we experienced a mismatch between our clinical training received and the role we were expected to play in the prison. We were placed in a space that felt dangerous, frightening, and for which we felt unprepared. By chance, we learned that each of us who was doing this prison work, each in a different prison, began to use online shopping as a way of coping with this anxiety as a means of virtual escape from our work environment. Common themes of powerlessness, loss of control, loneliness, feeling restricted and the need to escape emerged as motivators behind our online shopping. Online shopping created fantasy spaces where our individuality felt acknowledged, and where we experienced instant gratification through receiving tailored packages. Online shopping provided us with a regressive escape from daily work experience of a prison system dominated by locks, restrictions, and powerlessness and where people, including those providing mental health services are reduced to numbers in a harsh and rigid bureaucratic system. By way of conclusion, we reflect on the potential use of online technologies as a way of escaping more generally, especially under current pandemic conditions. We suggest that though virtual spaces can be helpful, counsellors need to remain mindful of issues pertaining to enactment, projection, and transference.